Morality in the manuscript Hikayat Prabu Anom Volume 2: A study of Immanuel Kant's deontological ethics - Supriadi, Dedi; Alandira, Palendika (citeus, 2025)
This study examines the representation of moral values in Hikayat Prabu Anom Volume 2 through the lens of Immanuel Kant’s deontological ethics. The analysis focuses on three main categories of moral values: divine moral values, social moral values, and personal moral values. The method used is descriptive qualitative with content analysis techniques applied to selected passages in the text that reflect ethical dimensions. The data is analyzed by identifying the actions and dialogues of central characters that embody moral principles such as duty, goodwill, and moral autonomy. The findings reveal that divine moral values are reflected in the characters’ submission to divine will and their sincere devotion through spiritual practices such as meditation and worship. Social moral values are evident in the just and wise actions of Prabu Anom, who shows concern for his people, honors the service of royal officials, and nurtures familial ties with fellow rulers. Meanwhile, personal moral values emerge through emotional self-control, consistency in principles, and the courage and responsibility demonstrated by the characters in times of conflict. The study concludes that Hikayat Prabu Anom Volume 2 is not only a heroic narrative but also a literary work rich in ethical values that align with universal moral principles and remain relevant in contemporary life.